Fresno County Bar Association Old-Timers Luncheon - Watkins, Howard::::::::: (1984)
Keynote speaker Appellate Court Justice Mildred Lillie, first woman attorney from Fresno County Lillie longest serving appellate court justice and judicial officer in California history